Determination of Nutritional Components of Beijing Traditional Roast Duck - Zhang, Hongxing; Rui, Yukui (Asian Journal of Chemistry, 2014)
Beijing roast duck is Beijing's famous specialties, but the nutritional components of Beijing roast duck is few. Eighteen kinds of essential amino acids and 8 kinds of essential mineral elements were measured in Beijing traditional roast duck. The results showed that The protein content is 23.67 g/100 g in Beijing traditional roast duck; the descending order of amino acid composition is Arg > Glu > Ala > Pro > Ser > Gly > Lys > Leu > Thr > Tyr > His > Met > Val > Phe > Ile > Asp > Hyp > Cystine while the descending order of these mineral elements is K > Mg > Ca > Fe > Zn > Cu > Mn > Se.